Effect of Carbenicillin on Somatic Embryos Formation of Papaya (Carica papaya L. var. Eksotika I) - M. B, Mohamad Fhaizal; P, Vilasini; A. R, Noorsaadah; K, Norzulaani (Malaysian Journal of Science, 2006)
Embryogenic callus could be established from immature embryo of Carica papaya L. var. Eksotika I after 3 - 4 months of culture on Callus Induction (CI) medium. Embryogenic callus was successfully induced (100 %) on CI medium supplemented with 250 mg/L Carbenicillin plus 10 mg/L 2,4-dichlorophenoxyacetic acids (2,4-D). Transparent somatic embryos then proliferated from the light brown friable embryogenic callus. Carbenicillin that was frequently used as an antibiotic to prevent fungal contamination in in-vitro cultures was found to stimulate the growth of somatic embryos of Carica papaya L. var. Eksotika I. Somatic embryos were maintained in a medium containing either reduced or without 2,4-D. The cultures could be maintained for a period of 5 - 6 months with no apparent loss of regenerative potential. The somatic embryos germinated on Germination (G) medium supplemented with 0.2 mg/L 6-Benzylaminopurine (BAP) and 2.0 mg/L 1-Napthaleneacetic acids (NAA) produced high regeneration frequency (88.41 %) with initial development of hypocotyls followed by rapid growth of plantlets. The in vitro shoots were readily rooted in G medium supplemented with 0.5 mg/L Indole-3-butyric acid (IBA) with 75 % successful rate.